Gallbladder stone incidence and prevalence in Germany: a population-based study - Kratzer, Wolfgang; Klysik, Magdalena; Binzberger, Andreas; Schmidberger, Julian; for the EMIL-Study group (Zeitschrift für Gastroenterologie, 2021)
Background We aimed to determine the prevalence and incidence of gallbladder stones in a random population-based collective in Germany.Methods We determined the prevalence and incidence rates of gallbladder stones in a random population sample of 1909 individuals from the Echinococcus-multilocularis in Leutkirch (EMIL) study in 2002 and 380 individuals in a follow-up analysis in the year 2013. The sonographic analysis was performed with a Philipps HDI 5000 (2002) and IU 22 (2013) (Netherlands) transducer 1–5 MHz. Statistical analysis was performed using SAS Version 9.4.Results The prevalence of gallbladder stones was 3.8 % (69/1909) in 2002 and 10.8 % (41/380) in 2013. In 2013, the gallbladder stone prevalence was 15.1 % (26/172) in women, compared to 7.2 % (15/208) in men. No gallbladder stones were found in participants in the 18–30 or 31–40 age groups. The average annual incidence was 1.03 % in the 41–50 age group, 0.79 % in the 51–65 age group, and 0.63 % in the > 65 age group. The annual incidence was higher among women (1.04 %) than men (0.53 %). The age-associated annual incidence rates for women and men were 1.93 % and 0.5 % in the 41–50 age group, 0.8 % and 0.78 % in the 51–65 age group, and 1.06 % and 0.30 % in the > 65 age group.Conclusion For the investigated German collective from 2002 to 2013, the average annual incidence of gallbladder stones was 0.75 %, with a higher incidence rate among women. These results are consistent with data from comparable international studies.
Keywords: ultrasonography; prevalence; incidence; gallstone disease; Germany